Procedure Time and Students’ Perception Comparing Full Arch Digital Scans with Conventional Impressions: A Cross-Over Randomized Experimental Trial - Hayam A. Alfallaj; Mohammed A. Alsaloum; Sahr H. Altuwaijri; Omar S. Aldibasi; Lubna T. Alkadi (International Journal of Dentistry)
Purpose/Objectives. Dental students are being introduced to intraoral digital scanning during their undergraduate dental education. Usually, the conventional impression technique is introduced before the digital scanning technique. This study compares the procedure duration, students’ preference, and perceived procedure difficulty level after students’ initial preclinical exposure to either digital scanning using CEREC Omnicam intraoral scanners or conventional impressions using vinyl polysiloxane impression material. Methods. Ninety-six dental students each prepared tooth #36 for an all-ceramic crown on typodont models and were then randomly assigned into either group A: performed digital scan first, or Group B: performed conventional impression first. Procedure time was recorded for both. Immediately following each procedure, students indicated their perceived procedure difficulty. After exposure to both techniques, they selected their preferred one. Results. There was a statistically significant difference between the mean procedure time of both techniques (P<0.0001), where students spent 663.76 ± 442.50 seconds to complete the conventional impression and 293.32 ± 181.49 seconds to complete the digital scan. Females were significantly faster in completing the conventional impression compared to males. On the contrary, male students were faster in digital scanning than female students. There were no carryover effects in the duration and the initially performed procedure. 76% (73 of 96) of participants preferred digital scanning with no statistical significance shown between the preferred and initially performed procedure. Participants perceived conventional impressions to be more difficult than digital scans. There was a weak positive correlation between the VAS score and the procedure time for the digital technique (R = 0.25) and a moderate positive correlation for the conventional technique (R = 0.45). Conclusions. The digital technique was preferred and perceived as easier than the conventional among undergraduate dental students with no impression-making experience, suggesting their readiness for new technology uptake. However, no significant correlation was found between the initially performed procedure and preference.